Introduction of quality management system of educational institutions and formation of innovative pedagogical process - Yusupov Kholmirza Alisherovich (Research Parks Publishing LLC, 2020)
It should be borne in mind that the changes taking place in our society in the economic, social, political and cultural spheres also depend on the education system, which determines the intellectual potential of our country and is a key condition for its development. At the same time, the growth of intellectual potential, the development of quality will not only have an impact on the effectiveness of education, the improvement of the system in this area, but also significantly affect the growth of all areas of this social system. That is why one of the strategic directions in education today is the identification of innovative activities of educational institutions as a key factor. Understanding the need to reform the education system requires that educational institutions be involved in innovative processes in practice, to see themselves in an innovative space where they have the opportunity to create, and most importantly, to adopt concrete innovations.